2015
DOI: 10.1021/acs.jpca.5b08867
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of CN with F, Cl, O, and S Atoms: Attachment or Associative Detachment?

Abstract: Highly correlated ab initio wave functions within the UCCSD(T)-F12 approach have been used to map the potential energy surfaces (PESs) describing the reactivity of the CN(-) (X(1)Σ(+)) anion with neutral atoms present in interstellar media (F, Cl, O, and S). With the H atom, for comparison, the reaction [CN(-)((1)Σ(+)) + H((2)S)] evolves along the PES of the X(2)Σ(+) electronic ground state of HCN(-) (or HNC(-)) until the crossing with the X(1)Σ(+) electronic ground state of HCN (or HNC), where electron detach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Difficulties in both processes lead to frustrations or controversies in terms of the understanding of the chemical reactions and molecular properties. Recently, the PESs of anionic cyanogen halides (XCN – , where X = Cl, Br, or I) have attracted a great deal of attention, aiming to reveal the photodissociation dynamics of the isolated and solvated anion XCN – (refs ), dissociative electron attachment (DEA) to the neutral XCN, , and the collisional reactions between CN – and atomic targets . With respect to the neutral, XCN – can be further stabilized in its ground state X 2 Σ + by elongating the X–CN bond and maintaining the linear structure (e.g., BrCN – shown in Figure ).…”
supporting
confidence: 38%
“…Difficulties in both processes lead to frustrations or controversies in terms of the understanding of the chemical reactions and molecular properties. Recently, the PESs of anionic cyanogen halides (XCN – , where X = Cl, Br, or I) have attracted a great deal of attention, aiming to reveal the photodissociation dynamics of the isolated and solvated anion XCN – (refs ), dissociative electron attachment (DEA) to the neutral XCN, , and the collisional reactions between CN – and atomic targets . With respect to the neutral, XCN – can be further stabilized in its ground state X 2 Σ + by elongating the X–CN bond and maintaining the linear structure (e.g., BrCN – shown in Figure ).…”
supporting
confidence: 38%
“…For example, trap losses have been experimentally observed for the Rb + OH − system 23 . We have previously shown that choosing another alkali or alkaline earth atomic species would not lead to detachment 24 since the vertical detachment energy of MOH − depends on M. An other example is the CN − anion for which the AED reaction can occur for some collision partners despite having a large electron affinity (3.862 eV) 25,26 . In conclusion, it is difficult to rely on general molecular properties to predict whether or not to expect AED reactions at low temperatures without explicitly calculating both the anion and neutral PES.…”
Section: Introductionmentioning
confidence: 99%
“…The above reaction has been extensively studied computationally because of the challenge provided by the instability of the hydrogen cyanide to electron attachment processes [11,16]. It is essentially a recombination reaction that is exothermic to forming the neutral system and therefore markedly favoured at the low temperatures of many of the ISM environments.…”
mentioning
confidence: 99%